Beyond One-Size-Fits-All: Personalized Medicine and Future Directions in Sex-Based Psychopharmacological Treatment - Marianna Mazza; Francesco Maria Lisci; Caterina Brisi; Gianandrea Traversi; Eleonora Gaetani; Roberto Pola; Giuseppe Marano (MDPI AG, 2024)
Sex-related differences in psychopharmacology present unique challenges in both clinical and research settings. Recognition of sex differences in psychopharmacological treatment has increased in recent years, but a significant research gap regarding variations between men and women still exists. Biological factors, including hormonal fluctuations, genetic factors, and brain structure differences, contribute significantly to differential drug responses. Moreover, social determinants can influence the differential burden of psychiatric disorders between the sexes and may impact treatment plans. Incorporating sex as a key variable in personalized treatment programs and plans holds the potential to optimize efficacy and minimize adverse effects in psychopharmacology. Sex-related challenges in psychopharmacology necessitate a nuanced approach to treatment. Further research is needed to fully understand these differences and to develop guidelines for personalized medication management. By addressing these challenges, clinicians can improve treatment outcomes and enhance the quality of life of patients with psychiatric disorders.